Partisipasi Politik Gen Z dalam Demokrasi - Berliana Renata, Dea Zahira (Maliki Interdisciplinary Journal, 2025)
This article discusses the active participation of Generation Z in the democratic process, highlighting their unique characteristics as agents of change in the digital age. By utilizing social media, Gen Z not only voices their opinions, but also engages in protests, election campaigns, and advocacy on important social issues such as climate change and social justice. Despite their enthusiasm, this generation faces challenges, including disinformation and lack of political education. The article concludes that support from society and government is crucial to ensure Gen Z can effectively contribute to democracy, building a more inclusive and responsive future.